Strengthening Student Competencies in the Digital Era to Support the Sustainable Development Goals (SDGs) through a Guest Lecture on Artificial Intelligence, Augmented Reality, and STEM - Hikmawati Hikmawati; I Wayan Gunada; Syahrial A.; Nina Nisrina; Zeni Haryanto; Bahtiar (Unram Journal of Community Service, 2026)
The transformation of education in the digital era requires prospective teacher students to possess competencies in utilizing innovative learning technologies that are relevant to the needs of 21st-century education. This academic community service activity aimed to strengthen the competencies of students in the Undergraduate Physics Education Study Program, Faculty of Teacher Training and Education, University of Mataram, through the implementation of a guest lecture themed Artificial Intelligence (AI), Augmented Reality (AR), and STEM in physics learning. The activity was conducted on April 28, 2026, in a hybrid format involving two guest speakers. The implementation method consisted of three stages: preparation, implementation, and evaluation. The evaluation was conducted through a Google Form-based questionnaire distributed to participants to measure their responses regarding material content, speakers, implementation, benefits, and the impact of the activity on students’ level of understanding. A total of 131 participants attended the activity, consisting of students from various semesters and alumni. The results showed that the majority of participants gave positive responses regarding the relevance of the materials, the competence of the speakers, the quality of implementation, and the benefits of the activity in improving learning motivation, academic insight, technological literacy, and readiness as prospective physics teachers in the digital era. In addition, participants perceived that the materials on AI, AR, and STEM integration provided contextual and applicable learning experiences. This activity was proven effective in strengthening the competencies of Physics Education students and contributing to the achievement of the Sustainable Development Goals (SDGs), particularly in quality education, while also supporting the implementation of the Impactful Campus program in higher education.